Physiological seed quality and initial growth of Handroanthus impetiginosus seedlings under different levels of shading and substrates - Chaves, Pâmela Miranda da Silva; Silva, Jhonata Ribeiro da; Braga, Mariana de Oliveira; Marques, Niandro de Souza; Freitas, Alessandra Doce Dias de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The speciesspecies Handroanthus impetiginosus (Mart. ex DC.) Mattos, commonly known as purple ipe, belongs to the Bignoniaceae family. Could be used in recovery of degraded areas, landscaping or in permanent preservation areas, although there is a little amount of information about this species. Our goal in this project was to assess the seeds physiology by imbibition tests and considering germination of purple ipe seeds in different substrates and light restriction levels. For the imbibition test, seeds were immersed in distilled water and placed in two different temperatures (25 and 30 ºC) in a proportion of 100 seeds for 200 ml of distilled water. Checkpoints were set at 2, 4, 16, 24 and 48h. Light restriction tests involved 3 substrates: S1 (Soil), S2 (Sand + coconut fiber), S3 (Sand + Goat Manure) and three light conditions: 0%, 50% e 80%. During 75 days the following variables were considered: height, root collar diameter and leaf number. There were no differences observed between temperatures for the imbibition test and after 48h of imbibition almost became stable for both temperatures. Considering the light restriction test, we can deduce that the seedlings growth rate were affected by the substrates as well for the light conditions. S3 substrate with 50% of shadowing combination provided best outcome results.